THE IMPACT OF THE PROBLEM-BASED LEARNING MODEL ON IMPROVING MATHEMATICAL UNDERSTANDING AND CREATIVITY STUDENTS - Ruth Mayasari Simanjuntak; Siti Sadar Sulastri Lumban Batu (European Journal of Humanities and Educational Advancements, 2024)
The purpose of this study is to ascertain if the problem-based learning teaching methodology can improve students’ mathematics understanding and creativity when teaching class VII junior high school quadrangular material. This sort of study is a quasi-experimental study with all grade VII at state junior high scholl in Pegagan Hilir T.A 2022/2023 as the research population. Through the use of straightforward random sampling techniques, experimental class research samples for classes VII-4 and VII-3 controls were acquired. Techniques for gathering data include documentation, experiments, and observations. Data analysis with the observation evaluation sheet and independent sample t-test. According to this study, using the Problem Based Learning instructional style can help kids become more creative and better at understanding mathematics. Ttest analysis can be used to get this result.